Penggunaan Klorin Diffuser Mini terhadap Sisa Klor pada Air Bak Bilasan Cucian Terakhir Pedagang Angkringan di Dusun Pajangan, Sumberagung, Moyudan, Sleman - Jati Khairudin; Mohammad Mirza Fauzie; Herman Santjoko (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Escherichia coli is one of mandatory biological parameters of environmental health standard forwater media in terms of sanitation and hygiene purposes.The maximum level permitted is 0CFU/100 ml. Based on laboratory examination, the clean water used by angkringan food stallers for food utensils at last rinse, was positively containing E. coli. Chlorine compounds can killmicro-organisms in water, because the oxygen liberated from the hypochlorous compounds oxidizes some important parts of bacterial and make them damaged. A simple chlorination giveschlorine dose administered only in about 0,2-0,5 ppm. The application of chlorine compound into clean water at the rinsing sink of those angklingan merchants require a chlorine diffuser. Inthis study, the tool was invented in mini form with 20 holes of 1 mm diameter, and made fromused felt-tip marker. This study was aimed to descriptively determine the ability and effectiveness of that mini chlorine diffuser in producing residual chlorine after being used for washingfood utensils and cutleries. The water as the study objects were that of the last rinsing sink ofangkringan food stallers at Pajangan Hamlet of Sumberagung Village in Sleman Regency. Thestudy was conducted in six days and examining five samples per day. The residual chlorinemeasurements were performed by randomly sampling one out of the five rinsing and used theappropriate test kit. Based on the examination results, the average residual chlorine obtainedwere: 0,22 mg/l, 0,24 mg/l, 0,24 mg/l, 0,24 mg/l, and 0,24 mg/l. Therefore, it can be concludedthat the mini diffuser is able to produce residual chlorine at 0,2-0,5 ppm.